Survey of Ergosan additive effects on gain weight, perpetuity rate and food conversion index in Rainbow trout - Sh Notash; H Mirzaei; S Sadigh Eteghad (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2008)
Evaluation of the effect of Ergosan additive on growth rate, feed conversion index and survival rate of 1gr Rainbow trout hatchlings. The purpose of the present study was to evaluate the effect of consumption of Ergosan additive on production indices of 1gr Rainbow trouts namely growth rate, feed conversion index and survival rate. Thus the effect of this additive was investigated by selecting five experimental groups (one control and four treatment groups) each consisting of 1500 fish with a weight of 1gram reared in exactly identical conditions. The treatment groups were fed 1, 2, 3 and 4 kg/ton of Ergosan with their diet for 60 days and the data were then analyzed. According to the results, Ergsan had the best effect on the production indices of the third treatment group (3 kg/ton) (p